Rapid pulsed-field gel electrophoresis method for Streptococcus spp. - Thong, Kwai Lin; Mohd Nasir, M.D.; Goh, Y.L.; Ngeow, Y.F.; Parasakthi, N. (Malaysian Society for Molecular Biology and Biotechnology, 2001)
Pulsed field gel electrophoresis (PFGE) despite being a highly reproducible and discriminatory method for molecular subtyping of many bacterial pathogens has been criticised for being time consuming. We have developed a modified, rapid PFGE method for Gram positive bacteria, in particular, Streptococccus spp. Our method can be completed in only 3 days' time as compared to the standard procedure which required Lip to 6 days. We successfully applied this method on clinical isolates of Streptococcus pneumoniae (50) and Group B Streptococcus (50) obtained from the University of Malaya Medical Center with comparable results. The method for DNA preparation was reproducible when repeated analysis was carried out. The rapid method has the ability to process a large number of isolates in less time than the standard method. This will definitely enhance the rapid and accurate analysis of outbreaks of nosocomial or community acquired Streptococcal infections.